Application of the INR proton LINAC for development of methods of radiotherapy and nuclear medicine - Akulinichev, S.V.; Aseev, V.N.; Vasiliev, V.N.; Gavrilov, Yu.K.; Grachev, M.I.; Derzhiev, V.I.; Kokoncev, A.A.; Kokoncev, D.A.; Lazebnik, D.B.; Ponomareva, E.V.; Skorkin, V.M.; Yakovlev, I.A. (Вопросы атомной науки и техники, 2013)
The review of the results of researches in the field of proton therapy and contact radiotherapy (high-dose-rate brachytherapy) is presented. Medical beam formation elements for a wide range of proton energies were calculated, elaborated and tested with proton beams. These therapeutic beams cover most sizes and localizations of tumors. Researches of a new source for high-dose-rate brachytherapy with Yb-169 were carried out. This source has several important advantages compared to conventional sources. Experiments of activation of the new source at the INR Neutron complex were performed and therapeutic properties of the new source were confirmed. We also present in this paper the current status of the new target assembly for producing of some PET isotopes with 20 MeV protons.